PENGARUH PROMOSI PENJUALAN TERHADAP IMPULSE BUYING MAHASISWA UNIVERSITAS ICHSAN SIDENRENG RAPPANG PENGGUNA SHOPEE INDONESIA - Auliyah Nurwafiyyah; Sutrisno Sutrisno; Muhammad G. Try Heady S; Mariam Makmur (Universitas Ichsan Sidenreng Rappang, 2025)
This study aims to assess the influence of sales promotion on impulse buying behavior among students of Universitas Ichsan Sidenreng Rappang who are active users of the Shopee Indonesia e-commerce platform. As part of the digital-native generation, students are considered highly responsive to various promotional stimuli, making them more susceptible to unplanned purchases. A quantitative research approach was employed, using a survey method. The sample consisted of 86 purposively selected students from various academic programs who regularly use Shopee. Data were collected through questionnaires, and analyzed using simple linear regression, partial t-test, and the coefficient of determination (R²). The results indicate that sales promotion has a positive and significant effect on impulse buying, as evidenced by a t-value of 8.607, which exceeds the critical value of 1.662, and a significance level of 0.000 < 0.05. Promotional tools such as free samples, coupons, cashback, price discounts, direct gifts, and events were found to effectively capture consumer attention and trigger impulsive purchase behavior. The study concludes that Shopee’s sales promotion strategies are effective in stimulating unplanned buying decisions among university students. This research suggests that students should develop more conscious buying habits in response to promotional offers. Sellers are encouraged to strategically utilize available promotional features, while Shopee is advised to continuously innovate and implement ethical promotion strategies. Future research is recommended to explore additional variables that may influence impulse buying behavior in the digital marketplace.